Aplikasi Arsip Surat Fiskal Pada Badan Pengelolaan Pajak Dan Retribusi Daerah Provinsi Sumatera Utara UPT PPD Medan Selatan - Suhardi Suhardi (LPPM Politeknik LP3I Medan, 2021)
Regional Tax and Levy Management Agency is a regional agency organization that handles regional revenue affairs, especially in terms of taxation for motorized vehicles and regional levies in North Sumatra Province. UPT PPD Medan Selatan or better known as SAMSAT (One Roof Manunggal Administration System) is one of the Technical Implementing Units under the auspices of the North Sumatra Province BPPRD. In some parts of the work at UPT PPD Medan Selatan still need a letter as the medium, the letter that is often used is a type of certificate and this can be seen when handling vehicle mutations, the certificate is better known as a fiscal certificate. In the recording of fiscal certificates issued by UPT PPD Medan Selatan, they still record manually using the SAMSAT expedition book so that it is very ineffective and inefficient. Based on this phenomenon, the researchers designed a Fiscal Letter Archive Application using Java programming. The research method used is Applied research (applied research). The benefit of this research is to facilitate the filing of fiscal letters so that they are more efficient and effective.